Effects of group-based enrichment on the behaviour of squirrel monkeys (Saimiri sciureus) at the Singapore Zoo. - Han, Sharleen Niyan. (2009)
Enrichment devices were used to stimulate the squirrel monkeys at the Singapore Zoo and improve their well-being. However, single-use food-based enrichment devices—devices which allowed only one monkey to access for food rewards at one time—were found to increase intra-group aggression due to competition for the food in the devices. Hence, group-based enrichment devices—devices that allowed more than one monkey to access for food at one time—were compared to single-use devices and the aggression levels measured to determine if group-based devices were more favourable in reducing intra-group aggression. Stereotypic behaviour levels were also measured to ascertain if the enrichments provided could decrease stereotypy levels, a sign taken to indicate improved welfare. The results showed that in comparison to single-use devices, the use of group-based enrichment devices produced lower aggression levels similar to baseline levels, indicating that unlike single-use devices, group-based devices did not elicit increased aggression from food competition. The effect of the enrichment devices on stereotypic behaviour, however, differed for different individuals, as each individual’s usage of the devices and propensity to display stereotypic behaviour varied. The effect of enrichment on each individual’s welfare was thus unclear.